Identification and association of polymorphisms in CAPN1 and CAPN3 candidate genes related to performance and meat quality traits in chickens - Felicio, A. M.; Boschiero, C.; Balieiro, J. C. C.; Ledur, M. C.; Ferraz, J. B. S.; Michelan Filho, T.; Moura, Ana Silvia Alves Meira Tavares [UNESP]; Coutinho, L. L. (Funpec-editora, 2013)
Meat quality is an important feature for the poultry industry and is associated with consumer satisfaction. The calpain 1 (CAPN1) gene is related to the tenderness process of meat postmortem, and the calpain 3 (CAPN3) gene plays an important role in myofibrillar organization and growth. The objective of the present study was to identify polymorphisms in these genes and to determine the association between these polymorphisms and traits of economic interest in poultry. Eleven animals (F-1) from an experimental poultry population at Embrapa Swine and Poultry were used to identify the polymorphisms. Four single nucleotide polymorphisms (SNPs) were found in the CAPN1 gene, and one SNP was found in the CAPN3 gene. A polymorphism from each gene was selected for genotyping in 152 chickens from the Embrapa F-2 experimental population and 311 chickens from a commercial population. Polymorphism g.2554T>C (CAPN1) was associated with body weight at 35 to 42 days, thigh weight, breast weight, carcass weight, and meat lightness content. SNP g.15486C>T (CAPN3) was associated with thigh yield, thawing-cooking loss, and shear force. Results suggest the possibility of using molecular markers in CAPN1 and CAPN3 genes as a tool for performance and meat quality traits in poultry breeding programs.
Keywords: Calpain; Genetic marker; Poultry; Shear force